HEAT CAPACITY, VISCOSITY, AND CONFIGURATIONAL ENTROPY OF ALKALI TITANOSILICATE MELTS - A CALORIMETRIC TEST OF THE CONFIGURATIONAL ENTROPY THEORY APPLIED TO THE VISCOSITY OF LIQUID SILICATES - Ali Bouhifd M.; Sipp A.; Richet P. (My University, 1999)
The heat capacities of three sodium and potassium titanosilicate glasses and melts have been determined between room temperature and 1800 K. For all melts, the heat capacity decreases with increasing temperatures after a 30% to 53% rise at the glass transition. For both glasses and melts, the heat capacity is an additive function of composition, which indicates that the calorimetric anomalies are an intrinsic feature of the TiO2 component that depends neither on the relative abundances of SiO2 and Na2O or K2O, nor on the nature of the alkali cation. The viscosities measured for these and two other melts indicate that, as embodied by the Adam-Gibbs theory of relaxation processes, the considerable decrease of the melt configurational entropy results in a dramatic viscosity increase near the glass transition range. Consistent with the major influence of configurational entropy, structural relaxation in the glass transition range proceeds much more slowly for Ti-bearing than for Ti-free melts. These various features are attributed to important temperature-induced changes in short-range order around oxygen atoms, with strongly decreasing substitution of Ti for Si at lower temperatures constituting probably the main factor.